CAMIFICATION OF THE EDUCATIONAL PROCESS IN A HIGHER EDUCATIONAL INSTITUTION: THEORY AND METHODOLOGY - KOBERNIK, A.N; OSADCHENKO, I.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
In the article, based on the analysis of scientific sources and empirical material, the theoretical and methodological features of the gamification of the educational process in a higher educational institution are substantiated. It is pointed out that a significant difference between gamification and gaming technology of learning is that a future specialist involved in a gamified educational process, does not play by itself, but learns with the definition of the rules of learning, like a game. Generalized and clarified the criteria, the compliance with which determines the gamification of the educational process in a higher educational institution, in contrast to the classic version of using didactic games: clearly defined goals that provide motivation for students to participate in the game; logical and consistent rules that set the limits and framework for students to achieve their educational goals; creation of a story, a legend with dramatic plots accompanying the learning process in order to create a sense of involvement in students, a contribution to a common cause; the aesthetics of the game, which primarily includes elements of the game computer design of the training course (balls, levels / stages; badges; leaderboards; prizes, awards and rewards; progress ribbons; storyline; feedback); a stable system of measurable feedback to ensure that the learning objectives set by the students are achievable and the teaching staff follow the didactic rules. The following methodological approaches to the implementation of this innovation have been identified: global information-computer, since the "planet" is already involved in the global gamification of education, taking into account its tendencies towards informality and continuity, the predominance of "clip" thinking in the younger generation; technological; systemic and practice-oriented approaches.